2019
DOI: 10.17706/ijcce.2019.8.1.32-39
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Clinical Decision Support and Use of Machine Learning to Reduce Alert Fatigue

Abstract: Therapeutic duplication alert is one of the Clinical Decision Support Systems (CDSS) that was implemented to help physicians and other healthcare providers in making clinical judgements about the patients' management of therapy and decreasing medication errors. However, there were high override rates of these alerts by physicians as they were deemed to be of non-clinical significance. The quantity of the alerts fired by the system was high leading to "alert fatigue". Thus, the hospital administrators reached a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Thus, alert implementation will not increase the clinical decision value equivalently [58,59]. A context-aware solution based on machine learning should be conducted in future studies [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, alert implementation will not increase the clinical decision value equivalently [58,59]. A context-aware solution based on machine learning should be conducted in future studies [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…[10] Similarly, another study in Saudi Arabia found no significant difference in the number of medication errors discovered when one type of CDSS alert was activated versus when it was deactivated. [11] In other words, CDS systems are intended to aid in the sifting of massive volumes of digital data to recommend the next steps for treatments, alert physicians about available information they may not have noticed, or detect potential problems such as dangerous prescription combinations.…”
Section: Cdss In Health Carementioning
confidence: 99%
“…AI algorithms, such as the Pulmonary Embolism Result Forecast Model, can be deployed within CDS software enabling the use of case-specific recommendations; if, in the case of a patient presenting to the emergency department with intermediate pretest probability of pulmonary embolism, the patient-specific likelihood of a positive CT Pulmonary Angiogram study is now known, the patient and provider may engage in decision-making that could reduce low value imaging in a sizable portion of patients (Banerjee et al, 2019 ). More accurately matching recommendations to patient contexts can help reduce the overall number of alerts for clinicians and mitigate alert fatigue (Chen et al, 2020 ; Khreis et al, 2019 ).…”
Section: Opportunities For Ai-enabled Cdsmentioning
confidence: 99%